Patent portfolio structure for single technology companies - Hartwell, Ian P. (Cranfield University, 2004)
Single technology companies (STCs) are defined in this thesis as companies that (a) have the fundamental rights to a new technology, (b) have development of that technology as their core competence, (c) seek to exploit that technology primarily by licensing the patent rights, and (d) are driven primarily by 'technology push'. These factors often result in much of the value of the STC residing in its patent portfolio. This in turn may place significant - and often conflicting - demands on the Intellectual Property (IP) Manager of the company. A review of the literature reveals a lack of guidance for the IP Manager, exacerbated by inconsistent terminology. To provide the IP Manager with suitable tools, this thesis explores the logic behind patent portfolios, optimal patent portfolio structure for STCs and a risk management (RM) approach to patents. Three stages in the patenting decision process are identified together with associated responsibilities, some of which extend beyond the IP department. Fundamental concepts of external Risk Factors/intemal Objectives and Patent Relationships are also proposed. A real-life patent portfolio belonging to an actual STC is reviewed, with a previously abstract literature method being adapted to depict that portfolio. Several Patent Relationships are found and the hitherto unexplored characteristic of 'Advantage' is identified as a way of showing other Patent Relationships. When applied to a second real-life portfolio, this reveals a new model for patent portfolio structure - the three- dimensional Scope/Advantage/Integration diagram - as well as highlighting that portfolio structure is determined by Risk Factors and Objectives that will be different for each STC. The thesis finishes with an examination of patent risk, particularly patent invalidity. Invalidity modes in Europe and the US are considered in detail and a comprehensive review of patent data sources is carried out. Results from two previously unexplored data sources are found to be consistent with trends proposed in the literature.